PENGARUH FREE CASH FLOW, KINERJA KEUANGAN TERHADAP EARNINGS MANAGEMENT DIMODERASI CORPORATE GOVERNANCE - Dewi, Rina Pusvita; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of free cash flow and financial performance to the earnings management, and to test the influence of corporate governance in moderating the correlation of free cash flow and financial performance to the earnings management. The amount of research samples are 45 companies which are listed in Indonesia Stock Exchange in non-financial service field in reporting years of 2010-2014, these companies have been selected by using purposive sampling. The analysis method has been done by using multiple linear regressions analysis. Based on the result of this research, it can be concluded that free cash flow and profitability have positive influence to the earnings management; meanwhile leverage has negative influence to the earnings management. The audit quality is proven able to moderate the correlation of free cash flow and leverage to the earnings management, but the audit quality is unable to moderate the correlation of profitability to the earnings management. Top share is able to moderate the leverage correlation the earnings management, but it is unable to moderate the correlation of free cash flow and profitability to the earnings management.Keywords: earnings management, free cash flow, leverage, profitability, corporate governance